2010
DOI: 10.1371/journal.pone.0014138
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric Key Structural Residues in Symmetric Proteins with Beta-Trefoil Fold

Abstract: To understand how symmetric structures of many proteins are formed from asymmetric sequences, the proteins with two repeated beta-trefoil domains in Plant Cytotoxin B-chain family and all presently known beta-trefoil proteins are analyzed by structure-based multi-sequence alignments. The results show that all these proteins have similar key structural residues that are distributed symmetrically in their structures. These symmetric key structural residues are further analyzed in terms of inter-residues interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…In the case of the β-strand 2, a conserved hydrophobic residue located in the N-terminal side is labeled as CHR-β2N and in the same way that in the C-terminal side is labeled as CHR-β2C. We confirm that these conserved hydrophobic residues correspond well to the conserved residues proposed by Murzin et al [4] and Feng et al [24]. Murzin et al defined the conservation of hydrophobic residues in two proteins from the Cytokine superfamily and one protein from STI-like superfamily.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…In the case of the β-strand 2, a conserved hydrophobic residue located in the N-terminal side is labeled as CHR-β2N and in the same way that in the C-terminal side is labeled as CHR-β2C. We confirm that these conserved hydrophobic residues correspond well to the conserved residues proposed by Murzin et al [4] and Feng et al [24]. Murzin et al defined the conservation of hydrophobic residues in two proteins from the Cytokine superfamily and one protein from STI-like superfamily.…”
Section: Resultssupporting
confidence: 88%
“…This fact may indicate that these equally distributed hydrophobic residues need to form the symmetrical β-trefoil fold. Similar results were already obtained by Murzin et al [4] and Feng et al [24], and they revealed the relationships between conserved residues and 3D structures or interaction energies. Feng et al [24] also found "symmetric key structural residues" specific for the β-trefoil structure based on structure-based multiple sequence alignment of domains in five two-domain proteins with two β-trefoil structures.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The connecting loops of the beta strands are known to vary in length and structure and provide specificity for binding to ligands such as other proteins, DNA, lipid membranes, and carbohydrates. The ricin-type beta-trefoil fold is found in a number of lectin-binding proteins, including ricin, hemagglutinin (HA)-related proteins including the HA33 protein of Clostridium botulinum and its homologue in Clostridium acetobutylicum, Cry (Cry41Ab1 and Cry42Ab1) and Cyt (Cyt1Ca) of B. thuringiensis, and the mosquitocidal toxins (Mtx) produced by Bacillus sphaericus during vegetative growth (6,7,9,12,13). The most characteristic feature of the beta-trefoil fold domain in lectin-binding proteins is the presence of three spatially separated glutamine-X-tryptophan QXW 3 repeats although the sequence is not absolutely conserved (13).…”
Section: Resultsmentioning
confidence: 99%